Students’ Effort for Independent Learning Through Voluntary Extensive Reading - Nugraha, I Gede Made Artha; Artini, Luh Putu; Utami, Ida Ayu Made Istri (Journal of Educational Study, 2023)
This study was aimed at analyzing students’ effort for independent learning through voluntary extensive reading in which it was viewed from students’ reading motives and materials. This study was designed in the form of qualitative study by involving 30 junior high school students and the data were gained through observation, interview, and survey. The instruments were the researcher, observation sheet, interview guide, and questionnaire. The collected data were analyzed by using qualitative data analysis. The findings revealed that; 1) the English reading materials read by the students are the materials related to the school materials, fiction (story, novel), and news, 2) students have their motives in reading extensively, namely to gain experience and skills in English language, to learn new things, to be confident and to improve ability in using the language. This study suggested that teachers to encourage extensive reading in classroom.